Kualiti Hafalan Terhadap Prestasi Akademik Plus Tahfiz UiTM Shah Alam: The Quality of Memorization Towards Academic Performance of Plus Tahfiz UiTM Shah Alam (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
Memorization of al-Quran is a practice that can improve one's ability of memorization, apart from empowering one's soul and spiritual aspect in the endeavour to raise new generations adorned with quality education and to embellish one's character. In implementing the government's aspiration to encourage the production of 12,500 professional huffaz from varieties of background expertise by 2050 as a part of Transformasi Nasional 50 (TN50), UiTM answers the call by nurturing approximately 105 students as of now, in Plus Tahfiz that is offered as a co-curriculum program. The involvement of students from different fields is a challenge to ensure they are able to complete their memorization syllabus prior to graduation. This research attempts to study the effects of al-Quran memorization practised on a daily basis towards the students' academic excellence and the improvement of the students' character. The methodology employed in this research is by distributing questionnaires. The findings of this research suggest that al-Quran memorization imprints a positive impact on students' academic excellence based on the analysis of students' current CGPA. The implication of this research proposed that al-Quran memorization should be granted more emphasis and should be integrated with the academic field because the practice of memorization of al-Quran contributes significantly to the students' academic excellence and the development of their character.